Reinforced chloroprene rubber by in situ generated silica particles: Evidence of bound rubber on the silica surface. Issue 30 (22nd April 2016) - Kapgate, Bharat P.; Das, Chayan; Das, Amit; Basu, Debdipta; Wiessner, Sven; Reuter, Uta; Heinrich, Gert
ABSTRACT: Nano silica is generated in situ inside the uncrosslinked chloroprene rubber (CR) by the sol‐gel reaction of tetraethoxysilane (TEOS). This results in appreciable improvement in mechanical properties of the CR composites at relatively low filler content. Furthermore, exploitation of reactive organosilanes, γ‐aminopropyltrimethoxysilane (γ‐APS) in particular, in the silica synthesis process facilitates growing of spherical silica particles with a size distribution in the range of 20‐50 nm. The silica particles are found to be uniformly dispersed and they do not suffer from filler‐filler interaction. Additionally, it is observed that the silica particles are coated by silane and rubber chains together which are popularly known as bound rubber. The existence of the bound rubber on silica surface has been supported by the detailed investigations with transmission electron microscopy (TEM), energy filtered transmission electron microscopy (EFTEM) and energy dispersive X‐ray spectroscopy (EDAX). The interaction between rubber and silica, via bi‐functionality of the γ‐APS, has been explored by detailed FTIR studies. © 2016 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2016, 133, 43717. Abstract :